Identities of Transracial Adoptees: Outsiders Looking In? - G. Ramsey, Patricia; Mika, Kalyn (Anales de Psicología / Annals of Psychology, 2011)
This study focused on how transracial adoptees often identify as outsiders and what factors influence this perception. Five female Korean adoptees attending college participated in in-depth interviews about their racial/cultural identities and how they were formed. Several themes related to identifying as outsiders emerged in their responses. Although participants described close relationships with their adoptive families and European American friends, they also had experienced events and assumptions that undermined these connections. Likewise, when attempting to affiliate with Asian groups, they often felt excluded because of their lack of familiarity with Korean culture and language. Several found close connections with other adoptees or with multiracial or multicultural peer groups.